Fiscal and Monetary Policy Ethics as Principal of Islamic Economy Regulation in Indonesia - Ardiansyah, Mawar; Sukti, Surya (Universitas Trunojoyo Madura, 2024)
This study aims to examine the importance of ethics in the implementation of fiscal and monetary policies as the main instruments of macroeconomic management aimed at creating stability and public welfare. Fiscal policy involves managing taxes, subsidies, and budgets, while monetary policy focuses on controlling the money supply and interest rates. This study uses a qualitative descriptive method with a literature study approach, collecting data from books, journal articles, and other publications related to the topic of fiscal and monetary policy ethics. The analysis was carried out by identifying ethical principles such as fairness, transparency, and social responsibility in both policies. The results of the study indicate that the integration of ethical principles in fiscal and monetary policies is essential to ensure fair distribution of resources, transparent financial management, and avoidance of detrimental practices, such as usury and excessive speculation. Examples of the application of ethics in this policy include the implementation of zakat, waqf, setting the Highest Retail Price (HET), and sharia-based monetary management. In conclusion, fiscal and monetary policies based on ethics are not only able to maintain economic stability, but also support inclusive and sustainable development